A 2022 Update on Computational Approaches to the Discovery and Design of Antimicrobial Peptides - Guillermin Agüero-Chapin; Agostinho Antunes; Yovani Marrero-Ponce (MDPI AG, 2023)
The antimicrobial resistance process has been accelerated by the over-prescription and misuse of antibiotics [...]